DATASET OF POTENTIAL RHIZOMA POLYGONATI COMPOUND-DRUGGABLE TARGETS AND PARTIAL PHARMACOKINETICS FOR TREATMENT OF COVID-19 - Mu, Chenglin; Sheng, Yifan; Wang, Qian; Amin, Amr; Li, Xugang; Xie, Yingqiu (Elsevier, 2020)
Rhizoma Polygonati (Chinese name as 黄精, pinyin as huangjing), as medicine and food homology of Traditional Chinese Medicine, has been recently applied for the complex prescriptions of alternative medicine for treatment of COVID-19 but the mechanisms are largely unclear. Here using public database search and filtering the potential chemical compound based drug targets with COVID-19 targets mapped, the list of data were provided and suggested pharmacokinetic tolerating dose of selected natural compounds were further collected from database. The data provided is the supplementary as a reference showing the intersections of Rhizoma Polygonati druggable targets of lists from current database and potentially related ones targeting COVID-19.
Keywords: Huangjing; Rhizoma Polygonati; Traditional Chinese Medicine; COVID-19; Research Subject Categories::NATURAL SCIENCES; Research Subject Categories::MEDICINE